Formation of Adjectives Referring to Human Physical Traits in the Speech of the Svrljig Area - Savić-Grujić, Ana R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Our analysis focuses on all the adjectives which refer to human physical traits in the speech of the villages in the Svrljig area. This derivational analysis included more than 300 derivative adjectives which, from a synchronic point of view, belong to the category of derived words. The analysis included derivatives which have been formed through prefixation and suffixation, as well as derivatives which occurred as the result of compound-suffix derivation. Special attention was paid to suffixation as the basic and most frequently available means of adjective formation. Suffixes are represented in combination with the base they are bound to, with an indication of their productivity and meaning in derivational terms. A study of the material indicates that adjective derivation by means of suffixation is made possible with the use of 20 suffixes and suffix derivatives, 10 of which have one confirmation each. The greatest productivity has been found for the noun base and suffix –av (52) which a total number of recorded derivative adjectives is 200. The prefix-suffix derivation process is the least frequent, and thus only 12 adjectives were derived in this way. Contrary to the mainstream opinion that complex words are not characteristic of our diasystem, the derivation process involving adjectives referring to humans based on physical traits shows great productivity in the compound-suffix derivation process. More than 90 complex words were derived from the binding the suffix –av (4), -as / -es (54) and the zero suffix (37) to complex bases. Another difference compared to the literary language is reflected in the occurrence of various forms of one suffix, which came about as the consequence of vowel changes (-as / -es : -ast). It is also not infrequent that during derivation, various forms of bases are used, or that a nonproductive basis in one system is productive in another. So for example it has been confirmed that in the speech of the Svrljig area the suffix –av is bound to adjective bases or that the suffix -as / -es is bound to verbal bases, which is almost never found in literary language.